PERAN PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM MENYELESAIKAN KONFLIK PERKEBUNAN PLASMA POLA KEMITRAAN PT. TBS DAN KUD. PS DI KECAMATAN KUANTAN MUDIK TAHUN 2010 - Ratna Sari Dewi; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The study aimed to determine the role of Local Government District Kuantan Singingi to resolving smallholdings conflict partnership between Tri Bhakti Sarimas Company (PT TBS). and Prima Sehati corporation (KUD. PS) in the sub-district Kuantan Mudik. This study focuses partnership between PT. TBS and KUD. PS because it had many problems in the partnership. So that, needed the role of Local Government District Kuantan Singingi to resolving the problematic. This phenomenon become interest to studies and be the background of this research. So the authors make formulation the problems are: what is the causative factor of conflict smallholdings and how the role of Local Government District of Kuantan Singingi to resolving the conflict. Based on this background, the study aims to analyze the role of Local Government district Kuantan Singingi to resolving smallholdings conflict partnership between PT. TBS and KUD. PS The research method is qualitative, with descriptive research, the data collection done by observation, interviews and documentation. From the research of result, shows that the Role of Local Government district Kuantan Singingi to resolving Smallholdings Conflict Partnership between PT. TBS and KUD. PS are: Local Government District of Kuantan Singingi made facilitating to resolving the conflict like a meet room to facilitation the problem between the third of actor. while that the parliament of Kuantan Singingi done they role as a mediator to mediation resolving the problems. Parliament done hearing between PT. TBS, KUD. PS ant Pucuk Rantau citizen as a member of corporation. In this study, the authors concluded that the role of local government district Kuantan Singingi, Have made various efforts to resolve the conflict after clashes, but preferably, the local government district of Kuantan Singingi should resolve the conflict before conflict hurt many parties.Keywords: Conflict, Plasma Plantations, PT.TBS, KUD.PS, Local Governmen